Security Price Reactions to Initial Reviews of Common Stock by the Value Line Investment Survey - Peterson, David R. (Journal of Financial and Quantitative Analysis, 1987)
David R. Peterson, Security Price Reactions to Initial Reviews of Common Stock by the Value Line Investment Survey, The Journal of Financial and Quantitative Analysis, Vol. 22, No. 4 (Dec., 1987), pp. 483-494